1988
DOI: 10.1113/jphysiol.1988.sp017408
|View full text |Cite
|
Sign up to set email alerts
|

Current source density analysis of linear and non‐linear components of the primate electroretinogram.

Abstract: SUMMARY1. Wte have used the method of current source density analysis to locate the generators of harmonic electroretinogram (ERG) responses to contrast-modulated pattern and uniform-field stimuli in the primate retina.2. Sinusoidal steady-state analysis was used, with a stimulus temporal frequency of 8 Hz. Fundamental and second-harmonic response components were measured for the uniform-field response. The second harmonic of the average of contrast-reversal pattern responses obtained at a series of spatial ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(42 citation statements)
references
References 33 publications
1
40
0
1
Order By: Relevance
“…[1][2][3][4][5] The PERG stimulus isolates the ganglion cell response by using a reversing (ie, contrast modulated) checkerboard or grating pattern that carries no change in overall luminance over time (space-averaged luminance). If the PERG response is measuring retinal ganglion cell activity, it should be associated with the number of retinal ganglion cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The PERG stimulus isolates the ganglion cell response by using a reversing (ie, contrast modulated) checkerboard or grating pattern that carries no change in overall luminance over time (space-averaged luminance). If the PERG response is measuring retinal ganglion cell activity, it should be associated with the number of retinal ganglion cells.…”
Section: Introductionmentioning
confidence: 99%
“…This consists mainly of neural tissue, the activity of which is revealed by ERG techniques. With focal ERG, it is possible to provide information from the central retina, i.e., the macula, which has higher neuronal density than peripheral retina [32][33][34]. Some papers have shown that the pattern and focal ERG can become abnormal in diabetes before the onset of any visible vasculopathy [ [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Some papers have shown that the pattern and focal ERG can become abnormal in diabetes before the onset of any visible vasculopathy [ [23][24][25][26][27]. Experimental [32,42] and clinical [32][33][34] studies showed that 1F, 2F, and 2P components of a steady-state focal ERG arise from different retinal neurons. Using this technique, which was first performed in different retinal disorders [35], we have found a gradual loss of postreceptor neuronal function as a result of diabetes, despite intensive insulin therapy and good metabolic control as reported by mean HbAlc levels during the 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations